Search for diarrheagenic Escherichia coli in raw kibbe samples reveals the presence of Shiga toxin-producing strains - Peresi, Jacqueline Tanury Macruz; de Almeida, Ivete Aparecida Zago Castanheira; Vaz, Tânia Mara Ibelli; Hernandes, Rodrigo Tavanelli [UNESP]; de Carvalho Teixeira, Inara Siqueira; de Lima e Silva, Sonia Izaura; Graciano, Rejane Alexandre Silva; Pinheiro, Sandra Regina; dos Santos, Luis Fernando (Elsevier, 2016)
The aim of this study was to investigate the occurrence of diarrheagenic Escherichia coli (DEC) strains in raw kibbe samples. For this purpose, 70 samples of raw kibbe were collected from retail establishments and analyzed. Isolated bacterial strains that presented a biochemical profile of E. coli were screened by multiplex PCR for the genetic markers defining the main DEC pathotypes. Two strains belonging to O125:H19 and O149:H8 serotypes were positive for stx 1c genetic sequence and expressed the gene, being thus classified as Shiga-toxigenic E. coli (STEC). These strains were further characterized in respect to other virulence traits and susceptibility to antimicrobial agents. One of them presented the genes astA and lpfO113 and the other harbored only lpfO113. One of the strains was susceptible to all the antimicrobials tested but the other presented an intermediate profile of susceptibility to ampicillin. To the best of our knowledge this is probably the first description of O125:H19 and O149:H8 STEC serotypes in refrigerated raw kibbe and foods in general.
Keywords: Antimicrobial susceptibility profile; Kibbe; Shiga toxin-producing Escherichia coli; STEC; Virulence markers